Identificação de padrões de uso de “Phrasal Verbs” mais comuns : confluências entre léxico, córpus e interculturalidade - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
We take phrasal verbs (PV) as lexical items, formed by the sequence VERB + PREPOSITION or VERB + ADVERB. We deal with the pattern of use of PV, which, by observing the distribution in different linguistic registers, allows a study of levels of formality (formal and informal) and language modality (speaking and writing). Therefore, an integrated approach between lexicon, corpus and intercultural issues is necessary. Our theoretical-methodological foundation uses Corpus Linguistics(SINCLAIR, 1997, 2004; BERBER SARDINHA, 2004, 2010; BIBER; CONRAD; REPPEN, 2004; ALUÍSIO; ALMEIDA, 2006; OLIVEIRA, 2009; SARMENTO, 2010; MCENERY; HARDIE, 2011; LIU, 2011) and to the precepts of Interculturality (SARMENTO, 2004, CORBETT, 2010; NIETO, 2010; BYRAM, 2012; KRAMSCH, 2013; MELO, 2016) Based on information from the Corpus of Contemporary American English, the general goal of the present work is to describe the use of the 150 most frequent PV in the North American variant of the English language. The specific objectives are as follows: 1) to identify the distribution of PV in different linguistic registers; 2) point out a tendency to use PV in oral and written modalities; 3) to point out the tendency to use PV in formal and informal contexts and 4) to compare the occurrence of PV in a diachronic perspective: 2011 (LIU, 2011) and in 2020. Regarding to the materials used for the development of our study, we highlight the Corpus of Contemporary American English, Curricular Guidelines for the Language course (BRASIL, 2001) and the National Curricular Guidelines for the Initial Training of Teachers for Basic Education (BRASIL, 2020) and, finally, the dictionaries LONGMAN Dictionary of Contemporary English and Collins COBUILD Advanced Learner’s English Dictionary. The methodological procedures comprise nine steps, which involved document reading, PV list consultation (LIU, 2011), searches and observations on COCA and PV use comparisons. The preliminary results indicate that most of the PV analyzed are found in the following registers: fiction (N=53), TV/movies (N=40) and spoken (N=21). Come on featured a super hit in the TV/movies section that elevated it to number one considering frequencies per million. This fact shows us that the language of cinema, despite representing everyday uses, has its frequencies artificialized. Point out and carry out stand out in academic texts, but according to the data, they appear in different sections of the texts, as point out is more recurrent to highlight researchers' points of view on theoretical foundations, while carry out is more common to describe methodological procedures. LC can contribute substantially so that dictionaries can clarify nuances of the uses of PV in different communicative contexts.
Identification of the most common “Phrasal Verbs” use patterns : confluences between lexic, corpus and interculturality
Keywords: Phrasal Verbs; COCA; Registros; Linguística de córpus; Interculturalidade; Registers; Corpus linguistics; Interculturality; LINGUISTICA, LETRAS E ARTES::LINGUISTICA